2018
DOI: 10.9734/jocamr/2017/39229
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey of Medicinal Plants Used as Aphrodisiacs in Bauchi Local Government Area

Abstract: Background: An aphrodisiac can be defined as any type of food or drink that is capable of causing sexual desire or arousal, increase sexual potency and increase sexual pleasure. The use of synthetic aphrodisiacs results in unwanted side effects that are noxious to the patients, thus there is a growing need to look for aphrodisiacs of herbal origin with lesser side effects. Aim: The aim of the study is to conduct an Ethnobotanical survey of medicinal plants used as aphrodisiacs in Bauchi Local Government area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Thus, even short-term storage of chufa nodules at room temperature adversely affects their germination. Further experiments should demonstrate what time schedules and tem- Currently, one of the urgent problems for both Europe and Russia is to improve nutrition patterns of the population and increase the share of natural and environmentally friendly products in the daily diet (Konarev et al, 2019;Sabo et al, 2018). The main problem of such products is their short shelf life, while the use of chemical preservatives not only negates the benefits of a natural product, but also harms the human organism.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, even short-term storage of chufa nodules at room temperature adversely affects their germination. Further experiments should demonstrate what time schedules and tem- Currently, one of the urgent problems for both Europe and Russia is to improve nutrition patterns of the population and increase the share of natural and environmentally friendly products in the daily diet (Konarev et al, 2019;Sabo et al, 2018). The main problem of such products is their short shelf life, while the use of chemical preservatives not only negates the benefits of a natural product, but also harms the human organism.…”
Section: Resultsmentioning
confidence: 99%
“…The tree is mostly found in the wooded savanna region of Senegal to western Cameroon and is widespread throughout tropical Africa Burkhil 1985). Hymenocardia acida is mainly used for the preparation of aphrodisiac and for its anti-dysenteric effects (Burkhil 1985;2004;Sabo et al 2018). This species is restricted to the savanna zone of Nigeria, which is inundated by cattle grazing and agricultural activities.…”
Section: Family: Phyllanthaceaementioning
confidence: 99%
“…The Literature abound on high prevalence of sexual dysfunction according to the community survey in Ogbomoso, South west Nigeria involving male population aged 30 to 80 years (58.9%) (Oyelade et al, 2016), Ibadan hospital survey on 18-70 years old male population (55.1%) (Adebusoye et al, 2012) and in over 40 years old males in Turkey (69.2%) (Akkus et al, 2002). Ethnobotanical surveys of aphrodisiac plants in Nigeria have been published for Akwa Ibom state with 31 plants in six families (Erhabor et al, 2013) and Bauchi Local Government Area with 10 plants (Sabo et al, 2017). Elsewhere in Africa, Ajao et al (2019) reported 209 traditional aphrodisiac plants, but only 48 plants out of the 77 plants scientifically investigated (including Gloriosa superba, Mucuna pruriens, Sphenocentrum jollyanum and Morella serrata) were found to elicit activity by increasing testosterone levels in rats, index of libido, sperm motility and prolonged ejaculation latency.…”
Section: Introductionmentioning
confidence: 99%